2012
DOI: 10.1016/j.ihj.2012.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid stage I palliation for hypo-plastic left heart condition without a hybrid suite: Suggestions for developing nations

Abstract: Cardiac hybrid procedures are performed in modern, spacious, and highly equipped hybrid suites in developed countries. Organizing such expensive suites in countries with an emerging economy is difficult from both a financial and logistics point of view. We share our experience of safely performing a Hybrid stage I palliation procedure for Aortic atresia with ventricular septal defect on a 2-month-old infant weighing 3.35 kg using minimal resources in a conventional catheterization laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Another death occurred three months after completion of the first stage, secondary to decompensated cardiogenic shock due to a restrictive atrial septal defect, reflecting the difficulty of maintaining clinical follow-up continuity of our patients because of a lack of specialized professionals in the primary care network at our state. To minimize this matter, we have set up a specialized team for the treatment of complex pathologies [ 12 ] , since that there has been an increased number of cases referred to our care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another death occurred three months after completion of the first stage, secondary to decompensated cardiogenic shock due to a restrictive atrial septal defect, reflecting the difficulty of maintaining clinical follow-up continuity of our patients because of a lack of specialized professionals in the primary care network at our state. To minimize this matter, we have set up a specialized team for the treatment of complex pathologies [ 12 ] , since that there has been an increased number of cases referred to our care.…”
Section: Discussionmentioning
confidence: 99%
“…Among the patients studied, 50% already performed the second surgical stage, and 2 patients were not at the appropriate age and weight to perform this procedure. Because of the deaths occurred, we have tried to keep the continuous monitoring, monthly, which was only possible after assembling a specialized multidisciplinary team, as suggested by Anuradha et al [ 12 ] , to complement the assistance given to people in the public health care network.…”
Section: Discussionmentioning
confidence: 99%
“…Others have safely performed the hybrid stage I palliation for a hypoplastic left heart condition (aortic atresia with ventricular septal defect) in a two-month-old infant using minimal resources in a conventional catheterization laboratory. 15…”
Section: Hybrid Stage 1 Palliationmentioning
confidence: 99%
“…It has been suggested that the hybrid stage I is less costly, and can give more time to patients’ families in developing countries to arrange financial and medical support for the ulterior comprehensive stage I+II surgery. 36 Meticulous planning should be considered by all centers wanting to start programs to treat HLHS, which remains the most challenging of cardiac diagnoses to obtain consistent excellent outcomes in a sustainable fashion.…”
Section: Hypoplastic Left Heart Syndromementioning
confidence: 99%